2019
DOI: 10.7759/cureus.4805
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Strategies to Manage Physician Burnout

Abstract: Physician burnout is an emerging condition that can adversely affect the performance of modern-day medicine. Its three domains are emotional exhaustion, depersonalization, and a sense of reduced accomplishment among physicians, with the Maslach Burnout Inventory (MBI) being the gold standard questionnaire used to scale physician burnout. This concern not only impacts physicians but the entire healthcare system in general. There is growing awareness regarding the mental health of physicians and the consequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(124 citation statements)
references
References 42 publications
3
111
1
9
Order By: Relevance
“…Another study was done on neurosurgery residents showed that long and multiple shifts associated with burnout risk [4]. Another research emphasized the effect of stressful on-call duties, and long duty hours on the increase in the incidence of burnout [5]. In addition, a study suggested minimizing work hours and assigning health care workers to speci c rules in order to prevent physician burnout [16].…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study was done on neurosurgery residents showed that long and multiple shifts associated with burnout risk [4]. Another research emphasized the effect of stressful on-call duties, and long duty hours on the increase in the incidence of burnout [5]. In addition, a study suggested minimizing work hours and assigning health care workers to speci c rules in order to prevent physician burnout [16].…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…The questionnaire was composed of Likert items which measured the extent to which respondents agreed or disagreed with statements relating to the three major domains of the senior residents' wellness (16 items), ability to deliver quality health care (17 items), and medical education experience (16 items) (Appendix 2). The responses to each item were coded as strongly disagree (1), disagree (2), neither agree nor disagree (3) agree (4) and strongly agree (5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A summary of burnout literature appeared in Cureus (an "open access medical journal for a new generation of doctors and patients' appeal to the cross-disciplinary nature of medicine") [23]. We highlight this thorough review of the literature for its content, but also to draw our readers to the journal Cureus, which like JWellness, appears too good to be true.…”
Section: Burnout Descriptionmentioning
confidence: 97%
“…Approximately $4.6 billion in costs related to physician turnover and reduced clinical hours is attributable to burnout annually in the United States which represents approximately $7600 per employed physician each year [16]. In addition to the signi cant nancial burden, the overwhelming administrative duties in part due to the electronic health record (EHR), sti ing oversight by employers, loss of autonomy and control, and lack of colleague and organizational support contribute to provider burnout [7,11,14,[17][18][19].…”
mentioning
confidence: 99%